Environmental, social and economic sustainability in urban areas: a cool materials' perspective - Rosso, Federica; Franco, Stefano (TeMA - Journal of Land Use, Mobility and Environment, 2021)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships among urban planning, mobility and environment, through a collection of short scientific papers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Economy, business and land use section aims at presenting recent advancements on relevant topics that underlie socio-economic relationships between firms and territories. The present note tackles the topic of cool materials for urban areas, as a mitigation strategy to counteract climate-change related issues. The most recent developments about cool materials demonstrate how they can boost environmental, social and economic sustainability and resilience in urban areas.